2018
DOI: 10.1177/1078155218788707
|View full text |Cite
|
Sign up to set email alerts
|

Case series of unique adverse events related to the use of ibrutinib in patients with B-cell malignancies—A single institution experience and a review of literature

Abstract: Background Ibrutinib, a Bruton's tyrosine kinase inhibitor has reformed the treatment of various B-cell malignancies including chronic lymphocytic leukemia, mantle cell lymphoma, and Waldenstrom's macroglobulinemia. Although generally well tolerated, here we describe our institutional experience of unique adverse effects encountered with the use of ibrutinib in patients with B-cell lymphomas. Methods This is a retrospective observational study done at a tertiary care facility, to evaluate adverse events in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“… 19 , 20 These include early autoimmune skin lesions, palindromic rheumatoid arthritis, bullous pemphigoid, autoimmune haemolytic anaemia, autoimmune cytopenia, severe arthritic syndrome and autoimmune myelitis. 21 , 22 These, like the presented cases, have been found to be responsive to steroids. 21 , 23 Autoimmune phenomena have been postulated to be related to ibrutinib's inhibition of interleukin-2-inducible T-cell kinase, thereby causing a Th1 shift and a pro-inflammatory response of Th1 cells.…”
Section: Discussionsupporting
confidence: 69%
“… 19 , 20 These include early autoimmune skin lesions, palindromic rheumatoid arthritis, bullous pemphigoid, autoimmune haemolytic anaemia, autoimmune cytopenia, severe arthritic syndrome and autoimmune myelitis. 21 , 22 These, like the presented cases, have been found to be responsive to steroids. 21 , 23 Autoimmune phenomena have been postulated to be related to ibrutinib's inhibition of interleukin-2-inducible T-cell kinase, thereby causing a Th1 shift and a pro-inflammatory response of Th1 cells.…”
Section: Discussionsupporting
confidence: 69%
“…Intermittent cessation of ibrutinib was reported to provide neurological improvement. 10 The current case had a distinct entity with the development of PNP only, which was directly associated with the agent rather than with any cerebrovascular event. The treatment was discontinued when grade 3 polyneuropathy was detected and the patient's complaints completely regressed.…”
Section: Discussionmentioning
confidence: 72%
“…A recent case report series by Shaikh et al reported single adverse events such as palindromic rheumatoid arthritis, diffuse spongiotic dermatitis, bullous pemphigoid, recurrent hemorrhage, stroke, recurrent paronychia, intramedullary fibrosis, recurrent joint pains, pulmonary aspergillosis and autoimmune hemolytic anemia. 10 Mato et al recently reported four cases of pneumonitis associated with ibrutinib. 11 Cataracts were reported in 3% of the patients in a review by Byrd et al, and in the same study, tumor lysis syndrome, which is a very rare adverse event, was also reported.…”
Section: Discussionmentioning
confidence: 99%
“…Other inflammatory reactions include lobular/septal panniculitis (21%) and rare reported cases of Sweet syndrome, pyogenic granuloma, pyoderma gangrenosum, granulomatous dermatitis, SJS, bullous pemphigoid, exfoliative toxin-positive staphylococcal scalded skin syndrome, and cutaneous lymphoid hyperplasia or cutaneous pseudolymphoma (CPL). 294,295,[300][301][302][303][304][305][306][307][308][309][310] Finally, secondary BCCs and cutaneous SCCs are seen in up to 4% of patients treated with ibrutinib. 299,311 Table 1 lists in detail the types of dermatologic toxicities associated with BTK inhibitors.…”
Section: Btk Inhibitorsmentioning
confidence: 99%